Transformasi Digital: Pemanfaatan Learning Management System dalam Pembelajaran Literasi Al-Qur’an: Digital Transformation: Use of Learning Management System in Learning Al-Qur'an Literacy - Muntafi’ah, Umi; Rusdiyah, Evi Fatimatur; Tolchah, Moch. (Anterior Jurnal, 2024)
This research aims to analyze the use of a Learning Management System (LMS) to increase the effectiveness of Al-Qur'an literacy learning and analyze the role of technology in facilitating students' active participation in Al-Qur'an learning. The research method used is descriptive qualitative research using the library research method. The data collection technique is by examining theories from various book literature, journals, and research related to LMS and Al-Qur'an literacy that have been carried out. The sources were taken from books entitled Development of LMS SiCeria (Indonesian Smart Students) and AL-Qur'an Literacy: Tahsin-Tilawah Learning Model Based on Talqin Taqlid. The analysis technique goes through four stages, namely data collection, data reduction, data presentation, and the final step drawing conclusions and verification. The results prove that the LMS for learning Al-Qur'an literacy is one of the innovations in learning Al-Qur'an which is quite effective in the current digital era. By utilizing the LMS feature which can be used to store and create material to be taught, collect student assignments, and share links to teaching media such as videos, teachers can also assess their students' assignments and access them online. The use of LMS in learning Al-Qur'an literacy is very dependent on teacher innovation and student enthusiasm. The results theoretically and practically contribute to teachers and lecturers increasing their innovation in presenting Al-Qur'an literacy learning through LMS. Apart from preparing infrastructure, increasing human resources by providing training for teachers to integrate this LMS in the Al-Qur'an literacy learning process must also be prioritized.